STANDARISASI PARAMETER NON SPESIFIK EKSTRAK ETANOL DAUN PEGAGAN (Centella asiatica L.) DI DUA TEMPAT TUMBUH - Aulia Rahmaniati M; Maria Ulfah; Dewi Andini Kunti Mulangsari (Jurnal Inovasi Teknik Kimia, 2018)
Pegagan leaf (Centella asiatica L.) is one of the potential medicinal plants that are often used for the treatment of analgesics, anti-inflammatory and hepatoprotector. Because of the many benefits of leaf pegagan it is necessary to standardize the extracts to ensure the quality associated with the substance of identity, and the composition of the chemical content whose specifications are contained in the monograph as the quality requirements listed in Materia Medika Indonesia.This research is an experimental research. Samples in this study were obtained from Tawangmangu and Kediri then extract using maceration method with 96% ethanol solvent. Standardization of non-specific parameters of ethanol extract of bay leaf includes determination of moisture content, total ash content, acid unsaturated ash content, drying shrinkage, specific gravity and heavy metal contamination (Pb, As and Hg). The data of the research results are compared with the standard that has been set in the book of Indonesian Herbal Pharmacopoeia and the Book of Standardization of Natural Medicinal Material.The result of non-specific test of extract ethanol extract of gotu kola leaf from Tawangmangu obtained by water content 4,689% ± 2,165%, total ash content 3,12% ± 1,76%, acid soluble ash content 0,97% ± 0,87%, weight Type of 1.631 g / mL ± 1.277 g / mL, shrinkage dried 11.26% ± 3.355% and heavy metal contaminants 0.27 ± 0.519 mg / kg extract, As ˂0.005 μg / mL, Hg <0.001 mg / kg extract. While the result of ethanol extract of pegagan leaf from Kediri is moisture content 6,197% ± 2,489%, total ash content 4,42% ± 2,10%, ash acid unsaturated level 0,97% ± 0,98%, weight of type 1,630 g / ML ± 1,275 g / mL, shrinkage rate 3,51% ± 1,873% and heavy metal contamination Pb 0,30 ± 0,547 mg / kg extract, As ˂0,005 μg / mL, Hg 0,001 mg / kg extract. Based on these results both extracts have met the standard of non-specific parameters but the parameter content of acid soluble ash content of ethanol extract of pegagan leaf from both Tawangmangu and Kediri and drying dried from Tawangmangu does not meet the standard requirements of non-specific parameters. Keywords: ethanol extract of gotu kola leaf, non specific parameter, Standardization.